Exemplary elementary social studies : case studies in practice - Libresco, Andrea S.; Alleman, Janet; Field, Sherry L.; Passe, Jeff (Research in curriculum and instructions, 2014)
In many elementary classrooms, social studies has taken a back seat to English Language Arts and Mathematics in the wake of No Child Left Behind and Race to the Top This volume is not another hand-wringing lament. On the contrary, the elementary educators who have contributed to this volume have a positive set of stories to tell about how social studies can play a central role in the elementary classroom, how teachers can integrate social studies knowledge and skills throughout the school day, and how this learning can carry over into children's homes and communities.The seven case studies in this book, one at each elementary grade level, highlight exemplary teachers in whose classrooms social studies is alive and well in this age of accountability. At the end of each case study, each teacher provides advice for elementary teachers of social studies. Our hope is that elementary teachers and prospective teachers, elementary principals, social studies supervisors, staff developers, and professors of elementary social studies methods who study the stories that we tell can be empowered to return social studies to its rightful place in the curriculum.